Ecological-economic trade-offs in forest conservation: China’s public welfare forest compensation policy on farmers’ production factor reallocation and livelihood diversification - Jian Wei; Xiaotao Huang; Tianwei Xie; Hanxiang Luo (Frontiers in Forests and Global Change)
IntroductionChina’s public welfare forest compensation policy is a pivotal environmental governance tool, promoting ecological conservation and advancing the practice of Payments for Environmental Services (PES). While prior studies have primarily focused on short-term ecological or income outcomes, there remains a lack of research on the policy’s long-term influence on rural households’ production factor allocation and livelihood strategies across forestry, agriculture, and non-agricultural sectors.MethodsThis study employs panel data from 12,810 farming households in 18 counties across 9 provinces, spanning the years 2003 and 2007–2019. A differences-in-differences (DID) model is applied to evaluate the impact of the compensation policy on rural production behaviors, including inputs in forestry, planting, animal husbandry, and labor allocation.ResultsThe analysis reveals that the policy significantly reduces input use in forestry, especially among more actively participating households. It moderately increases non-agricultural labor supply—mainly through labor out-migration—but shows no significant impact on planting or animal husbandry. Although the policy supports under-forest economic activities, it fails to fully compensate for declines in inputs to bamboo, economic, and timber forests. Policy effects vary significantly across different household types, shaped by resource endowments and regional economic contexts.DiscussionThese findings provide robust, long-term empirical evidence on the production-side effects of ecological compensation. The study highlights the importance of designing more nuanced PES policies that account for household heterogeneity and regional disparities, aiming for greater equity and effectiveness in implementation.